A Strange Love of the Land: Identity, Poetry and Politics in the (Un)Making of South Asia - Sudipta Kaviraj (South Asia Multidisciplinary Academic Journal)
In this paper I shall try to explore how the idea of space in what we call ‘South Asia’ today got reconfigured by modernity. I shall explore three spatial conceptions of South Asia—strategic, geographic and cultural; and I shall try to explain the patterns of space-thinking underlying each one of them, show their connection with modernity, and observe why and how South Asia is still not a space that can be conceived in nationalistic or state terms as a space of belonging. Two political processes of modernity introduce a new kind of space-making—nationalism and state-formation. In the paper, I shall follow some significant points of this dual process—of the emergence of new state structures—of British colonial India—and its animation of the rise of variant forms of nationalism—in 19th century Bengal, in the Islamic imagination of the 20th century, and eventually through the institution of state-nationalisms in India, Pakistan and Bangladesh. These state forms and gestalts of affect make it impossible to think of South Asia as a space of emotional inhabitance—like India or Pakistan. Yet, despite this state-nationalist borders of consciousness, there still exist long-term historical commonalities which people spontaneously practice and enjoy—in food, material culture, literature, art, music—which have a deep and long history. This marks peoples of this region (not states) by a common intelligibility which is reflected in their easy commingling when outside their countries, and free of the pressures of state nationalism, or in artistic public spheres.